Artificial intelligence in sustainability reporting / Prof. Dr Corina Joseph - Joseph, Corina (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
Prof. Dr Corina Joseph has been invited as a plenary speaker at the International Conference on Economics, Business, and Economic Education Science (ICE-BEES) organized by Universitas Negeri Semarang, Indonesia, from 30th to 31st May 2023. The conference theme, 'Re-thinking the dynamization between environmental issues and adaptive technology for inclusive growth,' saw Prof. Corina delivering her speech titled "AI and SDGs: Resource-Based View Perspective." In the speech introduction, various definitions of Artificial Intelligence (AI) were provided. One of these definitions describes AI as the utilization of automated algorithms, robotics, or machines that mimic human cognitive functions, enabling them to perform tasks such as learning, identifying, analyzing, and problem-solving (Graham et al., 2020). The rapid progress of AI has been facilitated by the extensive use of other technologies like machine learning methods for structured data, modern deep learning, and natural language processing for unstructured data. Today, AI is being employed to tackle socioeconomic and environmental sustainability challenges, contributing to the achievement of the Sustainable Development Goals (SDGs). For instance, in realizing SDG 6 (Clean Water and Sanitation), AI is being utilized to improve crop yields and reduce water consumption in agriculture. Prof. Corina highlighted the success of PepsiCo, which has effectively employed AI to assist farmers in the field. By collecting over one million key data points about potato cultivation in North America, Latin America, and Europe, farmers can automating reporting and analysis processes. By leveraging AI technology, companies can streamline the gathering and analysis of data, enhancing the accuracy and reliability of their sustainability reports.